Pengaruh Pengetahuan Keuangan, Perencanaan Keuangan dan Kontrol Diri Terhadap Pengelolaan Keuangan Pribadi (Studi Kasus Mahasiswa Fakultas Ekonomika dan Bisnis Universitas 17 Agustus 1945 Semarang) - Sriyani, Anisa Ika; Nugraha, Asta; Aminah, Siti; Riyadi, Bambang (Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to determine the influence of financial knowledge, financial planning, and self-control on personal financial management in students of the Faculty of Economics and Business, University on August 17, 1945 Semarang. The population used in this study is students of the Faculty of Economics and Business who have taken financial management courses one and two with a population of 406 students. The sample size used was 81 respondents, with the sampling technique using the Proportionate Stratified Random Sampling method. The data source used is primary data, with the method of collecting data using a questionnaires. The data analysis technique used is multiple linear regression analysis. The results of this study show that financial knowledge has a positive and significant effect on personal financial management, financial planning has a positive and significant effect on personal financial management, and self-control has a positive and significant effect on personal financial management.